Determination of Phosphorus Removal Mechanism in Aerated and Unaerated Steel Slag Filter System as Secondary Treatment System for Textile Industrial Wastewater - Mohd Arshad, Nur Ain Nazirah; Hamdan, R. (International Journal of Integrated Engineering, 2022)
Phosphorus is the element that promotes growth in plant. However, over loading of phosphorus into surfaces water leads to severe environmental problems known as eutrophication. Improper treatments of phosphorus removal prior discharges from industrial effluent are one of the contributions to eutrophication. Textile effluent is one of the sources of phosphorus loading in surface water with concentration of 1-9 mg/L P. Since attentions are given in removing the color from the effluent, phosphorus are commonly ignored in wastewater treatment system. Thus, the study of phosphorus removal in textile wastewater is conducted using steel slag filter system under aerated (ASSF) and unaerated (USSF) condition. The filter was set up for influent pH range of 5.30-7.00 at primary treated wastewater for textile wastewater under aerated and unaerated condition. Sampling was done twice a week for 12 week and analyzed for Total phosphorus concentration. The Activated Carbon (ACF) filter in the existing treatment system is also sampled to compare the removal efficiency The USSF filter shows better removal than ASSF filter with 46% to 70% of efficiency removal. Meanwhile, the removal efficiency of ASSF is 37% to 66%. The adsorbate formed in ASSF is analyzed using SEM-EDX and the precipitation formed in USSF is analyzed using XRD. This shows that steel slag filter provides promising result in phosphorus removal.